Online Noise as Illustrated by Pitfalls and Biogeography Associated With Common Names for Puma concolor - Wood, Emma; Ambrosini, Angela; Wood, Karen; Demetrio, Christina; O'Malley, W. Connor; Stratton, Andrew; Elbroch, L. Mark (Frontiers in Conservation Science, 2021)
Noise is the non-target search results that people encounter when searching for a particular topic of interest; conversely, it is the cloud of distracting data that can obscure or deflect conservation communication. Online noise associated with large carnivores is particularly dense because their defining characteristics make them salient. Mountain lions (Puma concolor) exemplify noise associated with multiple vernaculars for a species in the crosshairs of conservation conundrums. We compared internet search results, Google Trends reflecting topic interest, use in science publications and sentiment in print and online media for P. concolor’s most frequent vernacular names, “mountain lion,” “cougar,” “puma” and “Florida panther.” Puma and panther exhibited greater noise and salience than cougar or mountain lion, but, results for mountain lion, followed by cougar, yielded the highest biological relevance. Online sentiment negatively correlated with biological relevance, with positive sentiment highest for the noisiest vernaculars, puma and panther. As conservation practitioners, we must recognize that public outreach is part of our scientific agenda and be conscious of crafting communication that reaches and resonates with our intended audiences.